Tax on electronic commerce between imposition and exemption - Bounouir ILYAS ZAKARIA, Mennad; Sayah, Hamza; Salaa, Soumai (Finance and Business Economies Review, 2020)
The topic of this study focuses on the problem of imposing or exempting taxes on electronic commerce, In light of the existing debate on the of e-commerce and the existence of a trend calling for exemption and another that supports the opposite, And that both directions have arguments and logical and realistic evidence. So our main focus is on discussions, problems and challenges on this topic, To consider the bilateral approach between e-commerce and the tax system is imperative to ensure the effectiveness and efficiency of the latter.